2015
DOI: 10.1007/s00167-015-3950-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of tunnel variability between trans-portal and outside-in techniques in ACL reconstruction

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…GBA values with different evaluation methods range from 50° to 90° (some studies used the adjacent supplementary angle as the GBA). 8,9,18,24,33 In this cohort, the GBA was defined as the angle between the femoral bone tunnel and the intra-articular part of the graft (the line connecting the femoral tunnel aperture and the tibial tunnel aperture). The mean GBA of 56° was in the lower range compared with previous studies, probably because of the surgical technique and evaluation method used in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GBA values with different evaluation methods range from 50° to 90° (some studies used the adjacent supplementary angle as the GBA). 8,9,18,24,33 In this cohort, the GBA was defined as the angle between the femoral bone tunnel and the intra-articular part of the graft (the line connecting the femoral tunnel aperture and the tibial tunnel aperture). The mean GBA of 56° was in the lower range compared with previous studies, probably because of the surgical technique and evaluation method used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The graft bending angle (GBA), the angle between the femoral bone tunnel and the line connecting the femoral and tibial tunnel apertures, 20,24 has been proven to influence stress within the graft, and it might be an important factor in graft healing within the joint and bone tunnel. 18,28,33 A higher GBA could lead to tunnel widening.…”
mentioning
confidence: 99%
“…This may influence the enlargement of the femoral tunnel, according to our results. In fact, in a recent paper Sim et al showed that the outside-in technique in ACL reconstruction is recommended over the traditional transtibial technique to prepare the anatomical femoral tunnel in ACL reconstruction [6]. Jagodzinsky et al [25] have shown how distribution forces are an important factor for femoral tunnel enlargement, assuming these forces are directed and may reduce or increase the enlargement of the tunnel.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the cause of tunnel enlargement is unclear; it is thought to be multifactorial, with mechanical and biological factors playing a role [3,4]. Among the biomechanical causes, there are the bungee and windshield wiper effects, which arise due to excess motion of the graft in the bone tunnel, or micromotion at the tunnel aperture by the graft with suspensory fixation [5][6][7]. However, it is controversial as to whether tunnel enlargement affects the clinical outcome [8].…”
Section: Introductionmentioning
confidence: 99%
“…На сегодня причина расширения костных каналов в послеоперационном периоде до конца не ясна. Однако все исследователи сходятся во мнении, что существуют как механические, так и биологические предпосылки к его развитию [8][9][10]. К механическим относят выбор типа трансплантата, способа фиксации и неанатомичную его позицию, приводящую к микро-или макроподвижности в пределах костных каналов бедренной и большеберцовой костей [11,12].…”
Section: Introductionunclassified